Livelihood Pathways of Indigenous People in Vietnam's Central Highlands Exploring Land-Use Change - Thái, Huỳnh Anh Chi (Advances in Asian Human-Environmental Research,, 2018)
This study focuses on impacts of the environmental and socio-economic transformation on the indigenous people's livelihoods in Vietnam's Central Highlands recent decades since the country's reunification in 1975. The first empirical section sheds light on multiple external conditions (policy reforms, population trends, and market forces) exposed onto local people. The role of human and social capital is examined again in a specific livelihood of community-based tourism to testify the resilience level of local people when coping with constraints. The study concludes with an outlook on implications of development processed which still places agriculture at the primary position livelihood, and pays attention to human capital and social capital of indigenous groups in these highlands.